Design of planar microwave sugar level sensor using circular split ring resonator (C-SRR) - Chong, Zi Kang (2022)

(untitled)
In Malaysia, diabetes is a serious health problem that affects more than 20% of adults over the age of 30. Although many studies do not prove any direct link between sugar intake and diabetes, but the association between sugar intake and diabetes is strong. Therefore, several low-cost microwave sensors are designed on the market to measure the concentration level of sugar in beverages. In this project, the circular split ring resonator (C-SRR) is used with a planar transmission line to form a microwave sensor. The size of the microwave sensors is set at 30 mm wide, 50 mm long, and 1.6 mm high. Before the printed circuit board (PCB) is manufactured, the resonance frequency of the designed microwave sensor will first be calculated, and then compared with the simulated resonance frequency in the ANSYS High Frequency Structure Simulator (HFSS). As a last step, the printed microwave sensor is used to figure out how much sugar is in the sample under test (SUT) by looking at its resonance frequency.